CURRENT ISSUES OF THE USE OF INNOVATIVE TECHNOLOGIES IN THE TEACHING OF WORLD ECONOMIC AND SOCIAL GEOGRAPHY - Makhmudova, Manzura Jurayevna; Nomonov , Ne’matillahan Naqibullohan ugli (Educational Research in Universal Sciences, 2023)
This article provides recommendations on improving the quality of education, its main directions, criteria and indicators, as well as the study of the state of practice, the formation of skills and skills of students in science, the application of innovative technologies on the basis of issues of development of economic and social geography, strengthening the tasks, capabilities of future geography teachers in teaching methodology.